The Implementation of A Child-Friendly School Programme In Strengthening The Profile of Pancasila Students Based on Religious Moderation In Elementary Schools - wulan, Rizki Isma Wulandari (Proceeding International Conference on Religion, Science and Education, 2024)
The fading of the nationalist spirit of the nation’s students due to the lack of implementation of Pancasila values and religious and cultural diversity in the school environment will cause cultural degradation due to the times. This research aims to analyze the implementation of the child-friendly school program in strengthening the Pancasila student profile through religious moderation. The research method used is a qualitative case study type. This research was conducted at the State Elementary School (SDN) 01 Ampenan, Mataram City, involving the principal, teachers, and students as research participants. Data collection techniques were obtained through interviews, observations, and documentation and then analyzed by data reduction, data presentation, and conclusion drawing. The results of this study indicate that 1) The implementation of the child-friendly school program can strengthen the profile of Pancasila students at SDN 01 Ampenan with various school activities such as ACIMAS, Beranyen Nyampah, Little Police, and other activities that can shape Pancasila values to students such as unity, tolerance, cooperation. 2) The implementation of a child-friendly school program based on religious moderation successfully supports the implementation of the Merdeka curriculum at State Primary School 01 Ampenan by integrating religious moderation in the learning process which can shape character values in students such as honesty, religion, democracy, tolerance, discipline, creativity, independence, responsibility, care for others and love for the country. 3) The impact of strengthening the profile of Pancasila students through religious moderation has a positive impact on students, namely creating a child-friendly environment, harmony, harmony, and a more inclusive environment, as well as increasing students’ understanding of tolerance between religions. Based on these findings, it is important to integrate Pancasila values through a Child-Friendly School Programme that promotes religious moderation in improving students’ nationalism as a strengthening of the Pancasila learner profile in the context of religious diversity.